Perbaikan Sifat Fisika dan Kimia Tanah pada Lahan Muara Sungai Progo pasca Rehabilitasi melalui Penanaman Bogem (Sonneratia sp) - Eny Faridah; Daryono Prehaten; Cahyono Agus Dwi Koranto; Winastuti Dwi Atmanto; Haryono Supriyo; Handojo Hadi Nurjanto (Faculty of Forestry Universitas Gadjah Mada, 2021)
Mangrove planting in Progo River Esturaine in Kulon Progo was hindered by its marginal conditions, where the land was dominated by very dynamic sandy substrat. This condition has caused the growth of various planted mangrove seedlings by Forestry UGM team (2015-2016) was very low. Nevertheless, it was found that Sonneratia can grow well in the location. It was expected that Sonneratia can improve site condition so it became suitable for the growth of other mangrove species. This research aimed to assess soil properties of Progo River estuarine after rehabilitation using Sonneratia. Characterisation of soil physical (texture) and chemical (salinity, pH, and soil organic matter) properties were conducted in the Laboratory of Tree Physiology and Forest Soil, Faculty of Forestry UGM. Soil samples were collected from Sonneratia plant area in various growing conditions. The results showed that growth of Sonneratia affected soil physical properties particularly increasing the proportion of clay and silt, but not soil texture class. In general, more proportion of clay and sand were detected in the bigger Sonneratia plants and in the outer section of root system. The growth of Sonneratia also affected soil chemical properties particularly soil organic matter but not soil pH and salinity.